Удосконалення обліку грошових коштів в контексті забезпечення платоспроможності суб’єкта господарювання - Kuz, Vasyl; Кіцен, Тетяна Олегівна (Видавництво "Молодий вчений", 2019)
Стаття присвячена удосконаленню обліку грошових коштів суб’єкта господарювання в контексті забезпечення його платоспроможності. Визначено актуальність проблематики обліку грошових коштів у контексті забезпечення сталого та стратегічного розвитку суб’єкта господарювання. З’ясовано сутність й видозміни понять «грошові кошти» та «платоспроможність» у ринкових умовах господарювання. Визначено класифікацію грошових коштів відповідно до нормативних актів та з’ясовано важливість їх раціонального поділу для організації аналітичного обліку на основі якого формується інформаційне забезпечення управління платоспроможністю суб’єкта господарювання. Визначено мету та завдання управління грошовими коштами. Ідентифіковано основні проблеми обліку грошових коштів суб’єкта господарювання й шляхи їх вирішення. Наведено один із напрямів вирішення загально визначених проблем, що забезпечить підвищення інформаційної цінності облікових даних при прийнятті управлінських рішень. The article focuses on improving cash accounting in the context of the providing enterprise’ssolvency. The relevance of cash accounting issues in the context of ensuring sustainable and strategic development of the enterprise is determined. The essence and changes of the terms «cash» and «solvency» in the market conditions are clarified. It is stated that cash accounting should be considered as a set of interconnected sequential, organizational, logical, settlement operations and procedures for generating information on accounts receivable and payable, payroll for employees, with accountable persons, other creditors, taxes and payables. The classification of funds in accordance with the regulations is determined and the importance of their rational division for the organization of analytical accounting is formed, on the basis of which the information support of the solvency management of an entity is formed. The purpose and objectives of cash management have been identified. The main problems of accounting of the cash of the economic entity and the ways of their solving are identified. One of the ways of solving common problems is investigated, which is the direction of improvement of organization and methodology of accounting, and directions of improvement of information support of cash flow management of the enterprise, improvement of organization and methodology of accounting of funds and directions of consistency of policies of management of cash and related objects. The theoretical and methodological provisions of the study have been brought to the level of specific proposals for the development of a new accounting account and the opening of analytical accounts to it, which will reflect the cash receipts from the sale of goods to obtain information on the enterprise’s solvency.
Improving Cash AccountIng in the Context of the Providing EnterprIse’s Soivency
Keywords: аналітичний облік грошових коштів; грошові кошти; грошові потоки; класифікація грошових коштів; управління грошовими коштами; платоспроможність; проблеми обліку грошових коштів; analytical accounting of cash; cash; cash flows; classification of funds; cash management; solvency; problems of accounting of funds